Planning for Ecotourism on the Coast of Maine - Springuel, Natalie (Maine Policy Review, 2000)
Ecotourism, or nature-related travel, is one of the fastest growing types of tourism. This is particularly good news for Maine, a state rich in scenery and outdoor recreation opportunities. However, as Natalie Springuel cautions, without good planning and good management, the impacts of ecotourism may harm the very resources that make it viable. Springuel describes four elements of good ecotourism planning and management that came to the fore during a recent set of interviews with ecotourism guides, environmental advocates, and tourism promoters. While Springuel endorses the growth in Maine’s ecotourism industry, at some point, she argues, it will be up to the people of Maine to decide how much of a good thing is too much.